Manual on statistics of international trade in services - United Nations; European Commission; International Monetary Fund; Organisation for Economic C0-operation and Development; United Nations Conference on Trade and Development; World Trade Organization (New York: United Nations, 2002)
The manual conforms and explicitly relates to the System of National Accounts 1993 and the fifth edition of the International Monetary Fund's Balance of Payments Manual. It is jointly published by the United Nations, European Commission, International Monetary Fund, OECD, United Nations Conference on Trade and Development, and the World Trade Organization.
Includes bibliographical references (p. 172-173) and index.
opc 20/12/16
Loans
Keywords: Service industries; International trade